LINEAR OPTIMIZATION AND EXTENSIONS : PROBLEMS AND SOLUTIONS - DIMITRIS ALEVRAS; MANFRED W PADBERG (NEW YORK SPRINGER, 2001)
It covers the areas of linear programming and the optimization of linear functions over polyhedra in finite dimensional Euclidean vector spaces.
Keywords: MATHEMATICAL OPTIMIZATION -- LINEAR PROGRAMMING